Strategies for evidence-based in head and neck cancer: practical examples in developing systematic review questions - Guerra, Eliete Neves Silva; Amorim dos Santos, Juliana; Coletta, Ricardo D.; De Luca Canto, Graziela (Frontiers in Oral Health, 2024)
A systematic review (SR) requires several steps to be conducted. A major and initial challenge is to formulate a focused research question that may have high scientific relevance to provide evidence-based results and strategies. This narrative mini-review aims to present different categories of systematic reviews currently applied in Head and Neck Cancers (HNC), focusing on the strategies to provide results for evidence-based decision making. The SRs identified were of intervention, diagnostic testing, prognosis, in vitro and in vivo studies, prevalence, and epidemiological studies, and of association and risk factors. Focused questions that define the type of review, whether it is a therapy question (intervention), a question of prevalence or an outcome (prognosis) of disease, are discussed. Additionally, the importance in building interesting research questions and following all proposed steps to produce quality evidence are highlighted. This narrative mini-review may guide future research by showing how to perform and report relevant evidence in terms of HNC.